PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KARYAWAN PADA CV. GRAHA INDAH SARI - Humaidhi Semendawai (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
The problem of this research is as follows: Does the leadership style affect the motivation of employees at CV. Graha Indah Sari? While the purpose of this study was to determine and analyze about: The influence of leadership style on employee motivation at CV. Graha Indah Sari. The research design used is associative research, which is to see the influence and relationship between the independent variables consisting of: leadership style (X) and the dependent variable, namely employee motivation (Y), and to test the hypotheses that have been formulated. The population in this study were employees of CV. Graha Indah Sari with 24 employees. Because the population is less than 200 people, the entire population will be used as research respondents. The research results obtained are 1). The relationship between leadership and employee motivation at CV. Graha Indah Sari is very close-knit. 2). leadership has a significant effect on motivation. This value is shown from the hypothesis test using the r test, where the sig.r value is greater than the r table value, which means the hypothesis that motivation affects the leadership of employees at CV. Graha Indah Sari is significant.